Understanding preschool emergent science in a cultural historical context through Activity Theory. Issue 4 (3rd July 2016) - Sundberg, Bodil; Areljung, Sofie; Due, Karin; Ekström, Kenneth; Ottander, Christina; Tellgren, Britt
Abstract : The aim of this study is to explore how cultural factors interact with preschool teachers' shaping of activities with science content, and also how Activity Theory (AT) as a theoretical framework can be useful for examining interrelations within preschool systems. Qualitative data was collected from three preschools in the form of guided group discussions with preschool teachers, observations and video recordings of activities, and stimulated recall discussions based on the recorded practices. The preschools displayed diverse approaches for experiencing and learning science, some with great creativity. In all preschools learning was integrated with care, upbringing and play. To support children's interest and confidence was central. How science activities were shaped mainly depended on how children's interests were allowed to govern practice. The use of AT as an analytical tool was proven to be effective in identifying the elements, relationships and tensions crucial for understanding the framing of science activities.